Soils and soil fertility - Troeh, Frederick R. (Blackwell, 2005)
The book considers both urban and rural land use and includes discussions of lawns, artificial soils for greenhouse use, turfgrass for golf courses, and so forth. Weather, irrigagtion and drainage are given a chapter of their own,"water management" and environmental concerns are treated in the "Soil pollution"